Shariah non compliance risk in Bank Islam Malaysia Berhad / Wan Nur Aisyah Wan Adnan - Wan Adnan, Wan Nur Aisyah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
We live in a constantly changing environment. The changes happen without our own control. This applied to the Shariah non compliance risk in Bank Islam Malaysia Berhad. We will identify on how this risk happened. Is it because of the contracts and also to analyse on how Bank Islam Malaysia Berhad eliminates the risk? The objectives are to identify the guidelines that have been set by the Islamic scholars and analyse the strategies that used by Bank Islam Malaysia Berhad in managing Shariah non compliance risk. Next is to investigate the factors that can lead to this risk. Research methodology used in this research is qualitative research methodology includes interview. The basic guideline must be followed by Islamic Financial Institutions is must be issuance of relevant Shariah updates. This refers to a juristic opinion on financial issues given by the Shariah Board. These are steps taken by Bank Islam Malaysia Berhad when the risk occurs. First is to stop any operations or doubtful transactions. Next is reporting this Shariah matter and refers to Shariah Risk Management Department. The institution experienced Shariah non compliance risk because internal factors include internal process, people and system while external factor is external events.